Implementasi Metode Weighted Moving Average (WMA) pada Peramalan Harga Pangan - Haryati Haryati; LM., Fajar Israwan (LPPM STMIK WIT, 2020)
Forecasting the price of food commodities needs to be done to provide a representation of prices in the coming period. Obtained from the six types in the price forecasting sample using the Weighted Moving Average (WMA) method, the forecast value uses the Mean Absolute Perscentage Error (MAPE) method to find out how many deviations from forecasting results. Below 10%, it was concluded that the WMA method can be made as a method in forecasting the price of food commodities